Doktrin Teologi al-Ma'un dan Perkembangan Muhammadiyah: Studi Naskah - Sopaat, Sopaat; Supriadi, Dedi; Supendi, Usman (UIN Sunan Gunung Djati Bandung, 2023)
This reseach is historical analysis study based on philological texts with the theme AlMa’un Theology. This text is a source of theological reference in the actions of the Muhammadiyah movement which is taugh repetedly, for months and even as a whole for years to its students. The study of Al-Ma’un’s Theology manuscripts is important to be research material, bearing in mind that the influence of Al-Maun’s Theology permeated the students and successors of the Muhammadiyah Movement in its pioneering era and its development both in the center of Yogyakarta and even spreading the Muhammadiyah ideology because of the spirit of sacrifice. With posssessions, time and energy because of the influence of theology that became this action. Including raising and developing Muhammadiyah’s charitable efforts in West Java in this time. Purpose, this study aims to reveal the strong influence or the Tehological Spirit of Al-Ma’u in the developments of Muhammadiyah social charity in the country including in the local area of West Java. The method used in this research is the content analysis method or the study of the contents of the manuscript, namely descriptive analysis and making this manuscript as material for historical (historical) studies. From the reseach results, it was found that the Al-Maun Theological Manuscript is an important text among the Muhammadiyah Movement containing the basics of studying the Spirit of the Humanne Social Action movement (good deeds) which shows the integrity of monotheistic faith in God. The Al-Maun tehological Manuscript begins with the cocept of Sufism: Tahalli, Takhalli, Tajali by KHA Dahlan, then it is connected with Groups of Socual verses, and one of them is used as the title of this Manuscrips and was written by KHA Dahlan’s student, KRH Hajid as Al-Maun’s theological Manuscript. Maun. Al-Maun’s theology is a text which is the reference of the Muhammadiah movement so that it gives an importnas influence on the development of Muhammadiyah to its students and follower in developing Muhammadiyah’s charitable endeavors in the country, including in West Java since the colonial period.